2014
DOI: 10.17311/sciintl.2014.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Variations Between Field Bean Cultivars Due to Sowing Dates and Foliar Spraying Treatments

Abstract: Background: Shedding phenomena of field bean plant usually took place in serious values especially for buds, flowers and immature pods leading to a great reduction in seed yield. Thus, the main objective of this study was to study the performance of some field bean cultivars under sowing dates and foliar treatments. Methods: Field experiments were carried out during 2011-2012 and 2012-2013 seasons to find out the performance of cultivars (Sakha 1, Sakha 2 and Giza 3 improved) under sowing dates (15th October,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 7 publications
12
8
0
Order By: Relevance
“…The lowest values were recorded by Sakha1 and Sakha3 genotypes, respectively, in the two seasons of study. These results were, in general, agreement with those reported by Mekky et al (2003) and Abido and Seadh (2014).…”
Section: Results and Discussion Effect Of Sowing Datesupporting
confidence: 94%
See 1 more Smart Citation
“…The lowest values were recorded by Sakha1 and Sakha3 genotypes, respectively, in the two seasons of study. These results were, in general, agreement with those reported by Mekky et al (2003) and Abido and Seadh (2014).…”
Section: Results and Discussion Effect Of Sowing Datesupporting
confidence: 94%
“…This varietal variation might be due to their differences in their genetic makeup. Such results are in agreement with those of Mohamed (2012), Badr et al(2013) and Abido and Seadh(2014).…”
Section: Results and Discussion Effect Of Sowing Datesupporting
confidence: 93%
“…temperature and light intensity which allow to better establishment and vegetative growth, hence formation good canopy to increasing photosynthesis process, which might interpret the increase seed yield /plant and this might account much for a good seed filling and subsequently higher seed index. These results are in the same trend with those found by Bakheit et al (2001), El-Gizawy and Mehasen (2009) and Abido and Seadh (2014) who reported that 100-seed weight was increased by delaying sowing dates. The application of zinc to faba bean plants exerted a significant influence on 100-seed weight in both seasons.…”
Section: -100-seed Weight (G):-supporting
confidence: 91%
“…temperature and light intensity which allow to better establishment and vegetative growth, hence formation good canopy capable to increase photosynthesis process. It is worthy to mention that there results are in good agreement with those obtained by Bakheitet al 2001, El-Gizawy and Mehasen (2009) and Abido and Seadh (2014).…”
Section: -Number Of Pods/plantsupporting
confidence: 91%
See 1 more Smart Citation